Expanding Nuclear Physics Horizons with the Gamma Factory (Ann. Phys. 3/2022). Issue 3 (8th March 2022) - Budker, Dmitry; Berengut, Julian C.; Flambaum, Victor V.; Gorchtein, Mikhail; Jin, Junlan; Karbstein, Felix; Krasny, Mieczyslaw Witold; Litvinov, Yuri A.; Pálffy, Adriana; Pascalutsa, Vladimir; Petrenko, Alexey; Surzhykov, Andrey; et al.
Abstract : Physics Opportunities with the Gamma Factory The front cover shows the principle of the Gamma Factory, the subject of this special issue, as covered by the fourteen Research Articles and the Review Article (2100284 ). Secondary photons are produced by scattering laser light on partially stripped ultrarelativistic ions.